Frequency dependent anisotropy of porous rocks with aligned fractures - Gurevich, Boris; Galvin, Robert; Mueller, T. (European Association of Geoscientists and Engineers, EAGE, 2011)
In fractured reservoirs, the wave induced fluid flow between pores and fractures can cause significant dispersion and attenuation of seismic waves. For waves propagating normal to the fractures this effect has been quantified in earlier studies. Here we extend normal incidence results to oblique incidence using known expressions for the stiffness tensors in the low- and high-frequency limits. This allows us to quantify frequency-dependent anisotropy due to the wave-induced flow between pores and fractures and gives a simple recipe for computing phase velocities and attenuation factors of P, SV and SH waves as functions of frequency and angle.